ACHIEVEMENTS OF WUSHU SPORTS BRANCH OF NORTH SUMATRA SANDA AT THE NATIONAL SPORTS WEEK FROM 2012-2024 - Hotma Dearma Purba; Novita Novita; Rahma Dewi (SOSIOEDUKASI, 2025)
The National Sports Week (Pekan Olahraga Nasional—PON) represents Indonesia’s highest multi-event sporting competition and serves as a benchmark for provincial sports performance development. This study analyzes the fluctuating competitive achievements of North Sumatra’s Wushu Sanda team at the 2012–2024 PON using the CIPP model (Context, Input, Process, Product). Employing a descriptive qualitative research approach, the study involved officials of the sports association, coaches, and Wushu Sanda athletes from North Sumatra who were directly engaged in athlete development and PON participation. Data were collected through interviews, document analysis, and observation. Data analysis was conducted descriptively by linking the research findings to the context, input, process, and product components of the CIPP framework. The findings indicate that, from the context perspective, North Sumatra’s Wushu Sanda occupies a strategic position as a leading regional sport with a strong tradition of achievement, yet faces intense national competition and psychological pressures during major events. From the input dimension, the availability of athletes, coaches, and institutional support is generally adequate; however, the quality of athlete readiness remains uneven, particularly in terms of mental resilience and competitive experience. From the process aspect, the effectiveness of athlete development programs emerges as a decisive factor in performance consistency, where inconsistencies in training programs, limited monitoring and evaluation, and the lack of integrated mental preparation negatively affect athlete readiness. From the product dimension, North Sumatra’s Wushu Sanda demonstrates consistent medal attainment across the 2012–2024 PON editions, yet has not achieved sustained optimal results, with its peak performance recorded at PON 2016. In conclusion, the competitive achievements of North Sumatra’s Wushu Sanda are the result of an integrated interaction among the context, input, and process components of athlete development. Strengthening the coherence and synergy of these three components is crucial to enhancing future performance outcomes of North Sumatra’s Wushu Sanda at the PON.